Masyarakat Bahasa - Puspasari, Atika; Puspasari, Atika (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2018)
Abstract: This study aimed to describe about language community or language users. The discussion covers language community concept, the characteristics of language community, and the socio-situational factors that underlie the language community. This study is a literature review based study. Therefore, this study used documentation technique as data collection technique. The data collected were all theoretical framework of all discussion above such as language community concept, the characteristics of language community, and socio-situational factors which underlie the language community. It was found that one of the factors that influence human behavior was situational factor. Human behavior is influenced by the environment/situation. These situational factors include: ecological factors, design and architectural factors, temporal factors, social factors, and psychosocial environmental factors.     Keywords: Language community, Socio-Situational Factor, and Characteristics.